(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fungal infections in agricultural seeds can significantly impact crop yield and quality. Lablab purpureus is an essential leguminous crop known for its nutritional value and versatility in various agroecological zones. This research paper aims to investigate the prevalence and severity of fungal infections in untreated and treated seeds of Lablab purpureus, exploring the effectiveness of seed treatments in mitigating fungal diseases. The study employed a comprehensive analysis of fungal species diversity, pathogenicity assessment, and seed germination rates between untreated and treated seeds. Seeds treated with captan fungicide were compared with untreated control seeds to assess their efficacy in reducing fungal infections. The findings of this research will aid in devising better strategies for seed treatment and disease management in Lablab purpureus cultivation, thus ensuring enhanced agricultural productivity.